2019
DOI: 10.1587/transcom.2018isi0002
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Absorber Made by Natural Rubber

Abstract: This paper proposes fabrication process of a pyramidal electromagnetic (EM) absorber made by natural rubber. The advantage of this research is to generate value-added latex from Thai rubber and to reduce number of chemical absorber by using natural rubber based absorber. The proposed absorber in the research is mainly made from latex with carbon black filler. The proposed absorber is in the form of rubber foam which provides suitable characteristics to serve as an EM absorber. The results of this research are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In addition, its high specific surface area benefits the filler–matric interaction. Work by Salayong et al [ 16 ] introduced an electromagnetic absorber made from natural rubber filled with CCB. Their work indicated that the performance of electromagnetic absorption increased as the amount of CCB increased.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its high specific surface area benefits the filler–matric interaction. Work by Salayong et al [ 16 ] introduced an electromagnetic absorber made from natural rubber filled with CCB. Their work indicated that the performance of electromagnetic absorption increased as the amount of CCB increased.…”
Section: Introductionmentioning
confidence: 99%